2006
DOI: 10.1189/jlb.0905526
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphonuclear neutrophils deliver activation signals and antigenic molecules to dendritic cells: a new link between leukocytes upstream of T lymphocytes

Abstract: Polymorphonuclear neutrophils (PMNs) are rapidly recruited to tissues upon injury or infection. There, they can encounter local and/or recruited immature dendritic cells (iDCs), a colocalization that could promote at least transient interactions and mutually influence the two leukocyte populations. Using human live blood PMNs and monocytederived iDCs, we examined if these leukocytes actually interacted and whether this influenced DC function. Indeed, coculture with live but not apoptotic PMNs led to up-regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
111
2
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 141 publications
(119 citation statements)
references
References 63 publications
5
111
2
1
Order By: Relevance
“…It has been previously demonstrated that both viable and PMNapo could modulate DC maturation [21][22][23][24]. Therefore, we examined whether PMN that underwent spontaneous apoptosis (PMNapo) could affect Mtbinduced maturation of iDC in culture.…”
Section: Resultsmentioning
confidence: 97%
“…It has been previously demonstrated that both viable and PMNapo could modulate DC maturation [21][22][23][24]. Therefore, we examined whether PMN that underwent spontaneous apoptosis (PMNapo) could affect Mtbinduced maturation of iDC in culture.…”
Section: Resultsmentioning
confidence: 97%
“…This interaction was driven by the binding of the DC-specific, C-type lectin DC-specific ICAM-grabbing nonintegrin to the ␤2-integrin membrane-activated complex 1 [36]. Interestingly, a recent report demonstrates that live neutrophils can deliver activating signals to immature DC, whereas via cell contact, live and apoptotic neutrophils can transfer heat-killed Candida albicans antigens to DC, allowing the latter to stimulate T lymphocytes [5]. We did not obtain any evidence suggesting that neutrophils may direct the migration of DC in our experimental setting.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the role of neutrophils goes well beyond simply being recruited to kill microorganisms and then die (for a review [15]). These cells can also migrate to draining lymph nodes [11,25,26] and establish contacts with DC [27], helping the latter cells to stimulate T cells [10]. We investigated the cooperation between neutrophils and DC and its impact on antigen presentation to T cells in the context of BCG vaccination against TB.…”
Section: Discussionmentioning
confidence: 99%
“…They can help macrophages to eliminate highly adapted intracellular pathogens, such as Mycobacterium tuberculosis [6][7][8] and Leishmania major [9]. They may be key partners of DC; we have shown that live human neutrophils activate DC and transfer Candida albicans antigens for T cell presentation in vitro [10]. We have also shown in vivo, in mice, that neutrophils migrate via afferent lymphatic vessels to draining lymph nodes, where they shuttle live M. bovis Bacillus Calmette GuØrin (BCG) and get in the vicinity of resident DC and T cells [11].…”
Section: Introductionmentioning
confidence: 99%